Pesantren, Madrasah, Sekolah, Dan Panti Asuhan: Potret Lembaga Pendidikan Islam Minoritas Muslim - Ismail Suardi Wekke (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2017)
Emeyodere boarding school is one of the Islamic educational institutions in the Muslim minority neighborhoods, Papua. The existence of boarding schools in the region of the majority is certainly bringing challenges in the form of a minimum figure of Islamic Scholar and teacher. To support the lack of it, the boarding school of Emeyodere trying to do improvements management sector of the boarding school where the leader of the boarding school was taken not from the circles among the public but rather Islamic Scholar around. So this boarding school not only preserve the specificity of the classic boarding school but also open to undertaking reforms. This study aims to explore the boarding school in areas of the minority with all the limitations of resources and the uniqueness of the management. The existence of boarding school it has uniqueness i.e. integrating of boarding schools, schools, Islamic school, Islamic boarding school, and orphanage. As other boarding school tradition, individual religious who personally presented with the seriousness of seeking religious knowledge, carry out the ritual of worship (a' maa lul yaumiyah), and others. In addition, boarding school combines the orphanage into the boarding school as a representation of the social religious boarding Emeyodere.